Effects of Monosodium Glutamate on 11- to 50-lb Nursery Pigs - A. B. Clark; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband; K. J. Touchette (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 1,134 nursery pigs (PIC 280 × 1050, 11.2 lb BW) were used in a 48-d growth study to determine the effects of monosodium glutamate (MSG; Ajinomoto Heartland, LLC, Chicago, IL) on growth performance. Pigs were fed 1 of 6 dietary treatments: 0, 0.5, 1.0, 1.5, or 2.0% MSG, or a high salt treatment formulated to match the sodium content of the 1.0% MSG treatment. Experimental diets were fed in 3 phases from d 0 to 12, d 12 to 26, and d 26 to 48. Phase 1 was in pellet form and phases 2 and 3 were in meal form. Pigs were randomly allotted to pens at weaning and pens were then allotted to treatment according to BW in a randomized complete block design with 7 replications per treatment. During phase 1 (d 0 to 12), no significant differences were detected among MSG treatments, but pigs fed the high salt diet tended (P<0.053) to have poorer F/G than pigs fed the 1% MSG treatment. In phase 2 (d 12 to 26), increasing MSG decreased (linear, P = 0.045) ADG, ADFI, and worsened F/G while pigs fed the high salt diet had decreased (P<0.001) ADG and poorer (P<0.001) F/G than pigs fed the 1% MSG diet. In phase 3 (d 26 to 48), no significant differences were detected among the MSG treatments however pigs fed the high salt diet had decreased (P<0.028) ADG and ADFI compared with those fed the 1% MSG diet. Pig BW was reduced (linear, P<0.016) on d 26 and 48 for pigs fed the MSG diets and pigs fed the high salt treatment had decreased (P<0.001) BW compared to pigs fed 1% MSG. For the overall nursery period (d 0 to 48), increasing MSG decreased (linear, P = 0.033) ADG and tended (linear, P = 0.095) to decrease ADFI. Furthermore, pigs fed the high salt treatment had decreased (P<0.009) ADG and ADFI and poorer (P<0.001) F/G compared to their 1% MSG counterparts. Results from this study indicate that feeding MSG may have had a negative impact on ADFI and therefore, subsequent BW and ADG. In addition, the high salt treatment formulated to match the sodium content of the 1% MSG diet had consistently poorer performance than the 1% MSG treatment, suggesting that high salt content may negatively affect pig growth. Further research is warranted to determine the effects of feeding monosodium glutamate to nursery pigs in diets balanced for sodium content.
Keywords: monosodium glutamate; nursery pig; growth